The Touristic Importance of Gyula Region in the New Destination Structure Defined in 2020 - Kis, Fruzsina; Bagdi, Róbert (Acta Carolus Robertus, 2022)
The management system and organisational structure of national tourism fundamentally renewed in Hungary in 2016, which had several new elements. The five determined ’important tourism developing areas’ as destinations became the new frame for developing tourism in 2016 and 2017. Destination system was also changed in 2020, when not only the official names and territorial range were overviewed, but also created eleven destinations with determining six new ones. Among these destinations, the Gyula region consists of the least number of settlements with only two (Gyula and Békéscsaba). The 613 thousand tourism overnights (520 thousands completed by Hungarias) in Gyula and Békéscsaba in 2019 account for determining as a destination. Our questionnaire research investigated how widely known the destination was among the respondents and also their opinions about the most important sights. The Medieval Gyula Castle and Bastion, the Castle Bath and Aqua Palace, and the Almasy Castle proved to most popular sights in Gyula. The centennial confectionery is also well-known (with a three-quarter rate) among the visitors. 57.7% of the respondents mentioned at least two motivations to visit Gyula, and around one-thirds of the respondents visited the exhibitions of the Castle of Gyula at least three times.